Memory Laws and Historical Justice The Politics of Criminalizing the Past - Barkan, Elazar; Lang, Ariella (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines state efforts to shape the public memory of past atrocities in the service of nationalist politics. This political engagement with the 'duty to remember', and the question of historical memory and identity politics, began as an effort to confront denialism with regard to the Holocaust, but now extends well beyond that framework, and has become a contentious subject in many countries. In exploring the politics of memory laws, a topic that has been overlooked in the largely legal analyses surrounding this phenomenon, this volume traces the spread of memory laws from their origins in Western Europe to their adoption by countries around the world. The work illustrates how memory laws have become a widespread tool of governments with a nationalist, majoritarian outlook. Indeed, as this volume illustrates, in countries that move from pluralism to majoritarianism, memory laws serve as a warning - a precursor to increasingly repressive, nationalist inclinations.
Chapter 1: Mapping Memory Laws -- Chapter 2: French Laws for a Better Past -- Chapter 3: "(De) Criminalizing the Past: Spain's Legal Response to History, Memory, and Historical Memory -- Chapter 4: Polish Memory Laws and the Distortion of the History of the Holocaust -- Chapter 5: Legislating Historical Memory in Post-Soviet Ukraine -- Chapter 6: Holocaust Remembrance, the Cult of the War, and Memory Law in Putin's Russia -- Chapter 7: Protecting Memory or Criminalizing Dissent? Memory Laws in Lithuania and Latvia -- Chapter 8: Criminalizing Denial as a Form of Erasure: The Polish-Ukrainian-Israeli Triangle -- Chapter 9: Memory Laws: The Continuation of Yugoslav Wars by Other Means -- Chapter 10: Communism v. National Socialism: Legislation as a Tool of Selective Historical Narrative in Hungary -- Chapter 11: The Perils and Limits of Memory Laws: The Case of Israel's 'Nakba Law' (2011) -- Chapter 12: Memory Law and the Duty to Remember the '1994 Genocide Against the Tutsi' in Rwanda.
Keywords: History, Modern; Europe-History.; Civilization-History.; Modern History; European History; Cultural History